¿Una armonía de contrarios?: Commedia dell'arte in Two Productions of Valle-Inclán's La marquesa Rosalinda. (4th March 2018) - George, David
Abstract: Through an analysis of two specific productions of Valle-Inclán's La marquesa Rosalinda, I explore the ways in which these can inform our understanding of the play. I argue that the 1912 premiere did not do full justice to its richness and complexity, and that the first part of its subtitle, 'farsa sentimental y grotesca', was overemphasised at the expense of the second. I contend that neither María Guerrero and Fernando Díaz de Mendoza — the wife/ husband partnership who were responsible for the premiere — nor newspaper critics of this and other productions during the following eight decades have fully appreciated the duality that is inherent both in Valle's designation and in the long history of the commedia dell'arte, four of whose characters play a key role in La marquesa . After contextualising the play within this commedia context, I make use of photographs of the premiere and of photographs and a sound recording of a 1970 Madrid production directed by Miguel Narros in tandem with designer Francisco Nieva, in order to argue that it is their understanding of the play's sonic and, more particularly, visual possibilities that truly uncovers its dramatic possibilities.